Morphological and phylogenetic characterisation of endophytic fungi associated with the grapevine flowers in China - Manawasinghe, Ishara S.; Li, Xinghong; Zhang, Wei; Zhou, Yueyan; Tang, Ximing; Chethana, K.w. Thilini; Yan, Jiye; Brooks, Siraprapa; Hyde, Kevin D (Phytotaxa, 2020)
The harvest from grapevines is berries which are derived from the flowers. Even though numerous studies have been conducted to understand the pathogens associated with grapes, less is known about the fungi associated with the flowering stage and their potential for infecting fruit as latent pathogens. In the present study, 99 endophytic strains were isolated from the calyptra of grape flowers of four different grape cultivars (Italia, Jingxiangyu, Kyoho and Zexiang). The isolates were Alternaria, Cladosporium, Diaporthe and Epicoccum species. Alternaria was the most abundant genus with 88 strains of A. alternata. Four Cladosporium species were identified including two new host records (Cladosporium ramotenellum and C. anthropophilum) and one new species (Cladosporium endoviticola sp. nov.). Diaporthe eres and a novel Epicoccum species (Epicoccum endophytica sp. nov) were also identified. This study provides evidence that some grape fruit pathogens occur as endophytes in flowers. The study enhances the current knowledge of grape pathogens and can be used to develop sustainable management strategies.